Time and thermal stability improvement of polyethylene ferroelectrets. Issue 24 (23rd February 2019) - Hamdi, Ouassim; Mighri, Frej; Rodrigue, Denis
ABSTRACT: Ferroelectrets with good piezoelectric coefficients have been produced based on cellular polyethylene (PE) via extrusion film blowing. The quasi‐static piezoelectric coefficient ( d 33 ) value obtained (935 pC/N) was well above typical values for cellular polypropylene (PP) considered as the workhorse of piezoelectric polymers. Here, a focus was made on increasing the time and thermal stability of cellular PE piezoelectric activity. To do so, specific thermal treatments were applied on the films to improve their microstructure. First, films crystallinity was increased via thermal annealing at 80 °C for 5 min leading to a 32% increase of the initial d 33 value as well as its time stability. However, thermal treatment did not give a significant thermal stability improvement because the treated films almost completely lost their piezoelectric activity (96%) at 80 °C. Therefore, the films were treated with orthophosphoric acid resulting in substantial charge stability improvements, especially at higher temperature. Overall, it was possible to increase the continuous service temperature (CST) of PE ferroelectrets from 40 to 80 °C, which is similar to the typical CST of PP. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47646. Abstract :